A percepção de alunos e do professor sobre o uso do aplicativo Duolingo na aprendizagem de inglês como segunda língua - Cappellari, Alexandre Fehlauer (Universidade do Vale do Rio dos Sinos, 2020)
In the connected global context, we can observe the constant growth in the use of technologies as an ally to the specific purpose of education, especially the learning of new languages. In the present scenario, there is a growing number of language learning applications, as well as the great popularity they achieve. This work aims to understand the role and the impact of the use of the Duolingo language learning application in learning English language by students from a university in southern Brazil. The research, with a qualitative approach, consisted, first, in the elaboration and application of an interview with the five participants to know their relationship with the English language. The group of research participants, language students in a university environment, in addition to continuing classes with the teacher and with the programmed material, used Duolingo to study the language, under the researcher's supervision. These students had the next seven weeks to study and complete the basic units of the application. At the end of the period, participants produced narratives describing the experience and impressions of using the application during the period. An interview was also conducted with the class professor, in order to verify her perception of the learning by the participant students. The results, derived from the analysis of the narratives, reveal that Duolingo shows itself as a powerful ally to the process of learning a second language, however it cannot be the only resource. Duolingo must be understood as an application considered part of the learning process and cannot replace traditional teaching methods. Some considerations about the application, in relation to the post method era are made, as well as a reflection on the role of the teacher in this teaching context, which includes the increasing use of technology.
Keywords: Duolingo; Aprendizagem; Inglês; Segunda língua; Duolingo; Learning; English; Second language; ACCNPQ::Lingüística, Letras e Artes::Lingüística